A CRITICAL PROVOCATION TO SOCIOLOGY FRONT OF BNCC - Birkner, Walter (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
This essay is a critique of contemporary sociology in Brazil. The starting point is a review of high school textbooks that reveals a hidden antithesis between concerns about the distribution of wealth and social inequality versus lack of interest in the causes of economic production and development. Suggesting attention to these factors, we advocate the reinsertion of Sociology of development, passing through corresponding themes, such as evolutionism, social capital, economics and the interdisciplinary method as a facilitator. From this perspective of justifying sociological renewal, we correlate such concerns with the assumptions of the National Common Curricular Base - BNCC, which is the guiding document of Brazilian Education since 2018.